Effects of fuel reforming on large-bore low-speed two-stroke dual fuel marine engine combined with EGR and injection strategy. (30th October 2020) - Zhu, Lei; Li, Bolun; Li, Ang; Ji, Wenxia; Qian, Yong; Lu, Xingcai; Huang, Zhen
Abstract: Large-bore low-speed two-stroke dual fuel engines have become an urgent need to relieve energy crisis and reduce emissions. In this study, the effects of fuel reforming on large-bore low-speed two-stroke dual fuel marine engine combined with EGR and injection strategy were investigated. With increase of injection advance angle, the ISFC increases slightly, and also NOx emissions increase, which indicate that the optimal injection timing is 12.5°CA BTDC in consideration of emission and fuel economy. A 10% EGR rate is selected for NOx reduction and pressure rise rate suppression, which might increase fuel consumption in lower combustion temperature. Subsequently, fuel reforming is applied for further fuel consumption optimization. Compared with the base case, ISFC is reduced by 7.80% by introducing 1.29% syngas, but NOx emissions are higher than IMO Tier Ⅲ limit emissions standards. After combined optimization, the indicated thermal efficiency could be increased from nearly 50% (base case) to 55% by 12.5 BTDC_E10_2.25% (pilot fuel injection timing is 12.5°CA BTDC, EGR rate is 10%, and γreforming is 2.25%). Compared with the base case, the NOx emissions increase, but still lower than the limit value of IMO Tier Ⅲ emission standards, while the ISFC reduce 9.45% by 12.5 BTDC_E10_2.25%. Base on the above discussion, it can be concluded that the collaborative strategy has great potential in improving the fuel economy and also controlling emissions standard of low-speed dual fuel marine engine. Highlights: Fuel reforming is used to optimize the performance of dual fuel marine engine. The NOx emissions are lower than the IMO Tier III limit value. The indicated thermal efficiency could be increased by 5%.